Pengembangan Sistem Informasi Penilaian Rumah Sehat Untuk Evaluasi Bidang Penyehatan Lingkungan dan Promosi Kesehatan di Dinas Kesehatan Kota Pontianak - Gandha Sunaryo Putra; Nurjazuli Nurjazuli; Atik Mawarni (Jurnal Manajemen Kesehatan Indonesia, 2016)
Activities of health house assessment evaluation have not been done by Pontianak City Health Office (CHO). To support evaluation of the activities, section of environmental sanitations needs high-quality information in order to have an accurate both plan and decision. Unfortunately, current data management still uses a manual system in which it has some weaknesses as follows: data management uses manual method and requires longer time to process; information is hard to be obtained and to be accessed; presented information is incomplete; reporting is often late; and data accurateness is not guaranteed. The aim of this study was to develop health house assessment information system to evaluate department of environmental sanitation and health promotion at Pontianak CHO. This was Pre-Experimental Design (One Group Pretest-Posttest Design). System development used a FAST method (Framework for the Application of System Thinking). Number of subjects was 5 respondents. This study was conducted from December 2014 to September 2015. The results of observation and interview were analysed using content analysis and described using balanced average score. Overall, balanced average score before developing the system was 7.51 whereas balanced average score after developing the system was 21.87 (difference=14.36). There were statistically significant differences (p<0.05) between before and after developing the system in terms of the accessibility, completeness, clarity, speed, timeliness, and accurateness. Information system of healthy house assessment after being developed was able to overcome the problems of accessibility, completeness, clarity, speed, timeliness, and accurateness of information. Therefore, Pontianak CHO needs to utilise the information system of healthy house assessment as a source of information to support evaluation of healthy house assessment activities at Pontianak CHO.